2020
DOI: 10.1109/access.2020.2967634
|View full text |Cite
|
Sign up to set email alerts
|

Towards Safety-Risk Prediction of CBTC Systems With Deep Learning and Formal Methods

Abstract: Communication-Based Train Control System (CBTC) system is an automated system for train control based on bidirectional train-ground communication. Safety-risk estimation is a vital approach that strives to guide the CBTC system to guarantee the safe operation of vehicles. We propose a deep learning method to predict safety-risk states that combined with formal methods. First, the impact factors are selected, and the movement authorization (MA) failure rate is calculated by statistical model checking. Then, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Liu et al 39 adopt statistical model checking to calculate failure rates to guarantee vehicles safe operations.…”
Section: Statistical Model Checking and Accident Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 39 adopt statistical model checking to calculate failure rates to guarantee vehicles safe operations.…”
Section: Statistical Model Checking and Accident Predictionsmentioning
confidence: 99%
“…As a new application and research direction, we can use statistical model checking for accident or failure predictions, Calder and Sevegnani 7 propose a stochastic framework considering discrete space and temporal logic to forecast failure time bounds and maintenance cost. Liu et al 39 adopt statistical model checking to calculate failure rates to guarantee vehicles safe operations.…”
Section: Literature Review and Research Motivationmentioning
confidence: 99%
“…Sydney trains conducted condition monitoring for inspections and prevention of overhead wiring teardowns using laser and computer vision technologies [163]. Similarly, deep learning has been implemented to conduct traffic signal detection [164], [165], predict train delays [166], detect rail fastener defects and ballast history [167]- [169], detect cracks in and the shape and location of bolts [170], inspect railway ties [134], predict safety risks in communication-based train control systems (CBTCs) [171] and to perform subgrade status inspections [172].…”
Section: Related Work In Railway Systemsmentioning
confidence: 99%
“…Around the year 2017, Farooq et al [7] evaluated the wireless communication network performance of the CBTC system and suggested that the system could be further optimized; Farooq and Soler [8] did a survey on the CBTC system, and the survey showed that many researchers believe that the combination of CBTC system and Internet of Things technology could develop the CBTC system. Specially, in the research of Wang et al [18,19] around 2019, they focused on the safety protection and communications of the CBTC system, and they improved the CBTC system's wireless communication system by the Q-learning method based on LTE-T2T and obtained excellent application results. Recently, Liu et al [20] focused on combining the CBTC system with artificial intelligence computing (AI Computing).…”
Section: Introduction: the Development Of The Mining Industry And The Cbtc Systemmentioning
confidence: 99%